Microencapsulation of Analgesics as an Analog Form of Medicine - Aidana Nakipekova; Bates Kudaibergenova; Arkady S. Abdurashitov; Gleb B. Sukhorukov (Pharmaceutics)
Objectives: This research focuses on the development of fabrication approaches for microparticles intended for controlled drug delivery. The primary objective is to identify the most suitable polymer type, particle size, and morphology for encapsulating a water-soluble crystalline drug. Optimizing these parameters may enhance structural stability and prolong the release of this active substance. Methods: The microparticles were fabricated through the encapsulation of a drug substance within a polymer carrier and employing polymer casting on prepatterned surfaces, followed by the loading of drug precipitates and the application of a sealing layer. The crystalline powder 1-allyl-2,5-dimethylpiperidol-4 hydrochloride served as the core cargo material, while the walls of these particles were composed of polylactic acid (PLA) and a poly (α-caprolactone) (PCL) in a 70:30 composition ratio. Results: The size and volume of the microparticles were found to be dependent on the geometric parameters of the template and the concentration of the polymer solutions. The study demonstrates the formation, physical dimensions, and particle count at varied polymer compositions and concentrations. The formation of the PLA and PCL mixture occurred solely through physical interactions. Scanning electron microscopy (SEM) and optical microscopy were employed to observe the appearance and physical dimensions of the microparticles. The obtained data confirm that tailored polymer compositions can yield consistent particle morphology and a suitable drug elution rate. Conclusions: The results indicate that microparticles sealed with an optimal polymer composition exhibit enhanced release properties. This finding highlights the feasibility of microencapsulation at precise ratios and concentrations of polymers to achieve the long-lasting effects of water-soluble drugs.